Análise comparativa das variações mofométricas entre diferentes populações de Meloidogyne exigua - D'Arc de Lima, Rosângela; Ferraz, Silamar (Revista Ceres, 2025)
A morphometric analysis of M. exigua was conducted through character measurements of 160 larvae, 160 females, and 100 males from 8 different populations. Among the studied characters, nine in each group, were selected to compare the populations by cluster analysis.